(untitled) (Carte Romanze, 2024)
The contribution traces the history of the musical editions of Lo ferm voler by Arnaut Daniel (pc 29.14) and, with specific reference to the décasyllabe, proposes an essential theory of rhythm, reconsiders the hypothesis on the origin of the verse and offers a model of rhythmic reconstruction.